Agregação de valor ao resíduo de madeira na zona urbana do município de Santarém-PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
The use of wood waste has several purposes, one of which is for the production of small objects, which can be considered an agroecological practice to minimize impacts on the environment. Therefore, the objective of this work was to quantify wood residues of the species muiracatiara (Astronium lecointei Ducke) for the manufacture of artifacts. By applying 13 questionnaires to artisans, furniture makers and merchants, socioeconomic information was collected, as well as the cost of production and selling price. Among the products with the highest waste utilization is the dolphin-shaped tray with 2,268 kg.ud-1. Toys are the most manufactured artifacts, but the profit margin is smaller compared to the muiraquitã necklace and pen, which have a profitability of 170.3%. The annual profit in the production was of R$ 47,524.00 and in the commercialization of R$ 37,982.40 for the annual volume of 1848 pieces. It is used in the production of artifacts 3.688m³.year-1 of usable residue and 0.745m³.year-1 of non-usable residue. Utilizing waste from furniture production can increase the profitability of furniture making by 42.9% per year. The production and sale of artifacts is a viable way to add value to wood waste from furniture making, minimize environmental impacts and contribute to the artisans' family income.
Keywords: Artesanato; Movelaria; Amazônia; CNPQ:: ENGENHARIAS